Control of Coccidiosis in Chickens Through Herbal Medicine - Fitrine Ekawasti; E Martindah (Indonesian Center for Animal Research and Development, 2019)
Coccidiosis caused by Eimeria sp. is an important disease in poultry industry. In Indonesia, the morbidity due to this disease in poultry reaches up to 90%. The clinical symptoms of coccidiosis vary depending on the age of poultry and the species of Eimeria. If coccidiostat is not properly used in control and eradication program, it will cause resistance and residue in meat and egg. This paper aims to describe the optimal control of coccidiosis without chemical substances by using natural herbs. Resistance cases to Eimeria sp. cause the anti-coccidia ineffective therefore a safe and effective coccidiostat is needed. Currently, coccidiosis control using natural medicines from herbs was reported to be effective, safe, free of side effects and cheaper. An integrated coccidiosis control program can be applied along with biosecurity, vaccination, prebiotics and coccidiostat from herbs. Control of coccidiosis in chickens with herbal medicines can increase immunity, appetite and reduce stress so that it can suppress Eimeria sp. infestation.